Community Partnerships - Thomas, Adrainne; Casale, Carolyn (Review of European and Comparative Law, 2020)
An egalitarian model of university-school partnerships starts with a theoretical frame of equity and social justice. This qualitative research study sought to understand high school students’ perception of community service through an intergenerational university-high school-elementary school partnership. Data analysis consisted of detailed notes collected from university faculty who oversaw the focus group discussions and two graduate assistants who took observational notes. These notes were analyzed and thematically organized. The findings indicate that the students enjoyed the experience and were highly motivated to complete and read their community themed book for the younger children in their community. This research contributes new knowledge to the field of community engagement and to the field of informal and formal education through its analysis of discussions on meaningful community service pertaining to university-school collaborative partnerships.